PENGARUH TINGKAT PENDIDIKAN DAN DUKUNGAN KELUARGA TERHADAP PEMILIHAN ALAT KONTRASEPSI PADA AKSEPTOR KB DI KOTA KUPANG - Kadek Dwi Ariesthi; Theresia Mindarsih; Arijanti Ulnang (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2020)
The rate of population growth in Indonesia which continues to increase is the reason for the creation of the family planning program. The community is given the freedom to choose the contraceptive method they want to control the number of children. In Kota Kupang, the number of NonMKJP acceptors was higher than that of MKJP acceptors. Non MKJP contraceptives affect hormonal, and if used for a long time will affect the health of the body. This study aims to analyze the effect of the level of education and family support on the choice of contraceptive methods for family planning acceptors in Kupang City. This research is an analytical study using cross sectional method. This research was conducted from May to June 2020. The data collected were primary data using a questionnaire. The number of samples in this study were 200 people, selected by random sampling technique The results obtained were that the level of education and family support were closely related to the choice of contraceptives for family planning acceptors in Kupang City